Oferta edukacyjna dla młodzieży w województwie lubuskim = Educational offer to the youth in the Lubuskie province - Narkiewicz-Niedbalec, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents data concerning educational offers of schools in Poland and in the Lubuskie province. In 1992 in Poland a reform of the education system began. Now primary school lasts 6 years, then there are 3 years of lower secondary school, then 3 years of high school or 4 years of technical college. In the 1970s and 1980s, 60% of pupils after elementary school attended vocational schools and 40% of them chose schools which ended with an exam. Only 10% of young people began studying.
Keywords: województwo lubuskie; szkolnictwo polskie; Młodzież - nauczanie